2023
DOI: 10.3389/fpls.2023.1052425
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling genetic variation among white spruce families generated through different breeding strategies: Heritability, growth, physiology, hormones and gene expression

Abstract: Tree improvement programs select genotypes for faster growth, at both early and late stages, to increase yields over unimproved material, and the improvement is frequently attributed to genetic control in growth parameters among genotypes. Underutilized genetic variability among genotypes also has the potential to ensure future gains are possible. However, the genetic variation in growth, physiology and hormone control among genotypes generated from different breeding strategies has not been well characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 72 publications
(145 reference statements)
0
1
0
Order By: Relevance
“…Previous studies on the heritability of Scots pine features associated to needles have found values between 0.30 to 0.88 (Donnelly et al ., 2016). However, additional gymnosperm species were shown to have low heritabilities for root-related features as root length (depth) and root:shoot ratio (Galeano and Thomas, 2023). In our study we found canopy traits to have high heritability values and moderate for root traits.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the heritability of Scots pine features associated to needles have found values between 0.30 to 0.88 (Donnelly et al ., 2016). However, additional gymnosperm species were shown to have low heritabilities for root-related features as root length (depth) and root:shoot ratio (Galeano and Thomas, 2023). In our study we found canopy traits to have high heritability values and moderate for root traits.…”
Section: Discussionmentioning
confidence: 99%